Pengaruh Gaya Hidup Terhadap Perilaku Konsumtif Mahasiswa Bimbingan dan Konseling Universitas Islam Negeri Sjech M.Djamil Djambek Bukittinggi - Yunita, Herma; Elviana, Elviana; Syawaluddin, Syawaluddin; Sari, Intan (Jurnal Educazione : Jurnal Pendidikan, Pembelajaran dan Bimbingan dan konseling, 2025)
This research is motivated by a phenomenon that occurs in guidance and counseling study program students at UIN Sjech M. Djamil Djambek Bukittinggi. There are several students who tend to exhibit consumptive buying pattern This study aims to determine whether there is an influence of lifestyle on the consumptive behavior of guidance and counseling students at UIN Sjech M Djamil Djambek Bukittinggi. This study uses a quantitative approach with a correlational type with a simple linear regression analysis method. The population in this study was 493 students. The sampling technique in this study was Proportionate Stratified Random Sampling. The sample in this study was 221 samples. The instrument used in this study was a questionnaire. Data analysis used to test the research hypothesis was simple linear regression. The results of the study showed that lifestyle influences the consumptive behavior of guidance and counseling students and the magnitude of the influence of lifestyle on consumptive behavior is 74.9% which is in the high category.